An integrated perspective of social exchange theory and transaction cost approach on the antecedents of trust in international joint ventures. Issue 3 (June 2017) - Khalid, Saba; Ali, Tahir
Abstract: This study investigates the antecedents of trust in International Joint Ventures (IJVs). Building on social exchange theory (SET) and transaction cost theory (TCT), we develop an integrated framework in which trust development requires two sets of antecedents: (1) social antecedents (prior alliance experience with partner, partner's cultural sensitivity and reputation, inter-partner communication, expected longevity of the IJVs), and (2) structural antecedents (interdependence, ownership share, resource complementary). The developed framework is tested using web-survey data collected from 89 IJVs established by Nordic firms in Asia, Europe and America. Empirical data analysis based on structural equation modelling suggests that a partner's cultural sensitivity and reputation, inter-partner communication, and expected longevity are the social antecedents from SET that enhance trust. From TCA, the structural antecedent of resource complementary develops trust, while balanced interdependence and balanced ownership are unrelated to trust. These findings have important implications for managers planning to form and manage IJVs.